NAFTA's Developmental Impact on Mexico: Assessment and prospects - Jean-Baptiste Velut (IdeAs)
This article assesses the developmental record of the North American Free Trade Agreement (NAFTA) in Mexico fifteen years after its implementation. After analyzing the evolution of trade and investment flows and their impact on employment and wage levels in the manufacturing and agricultural sectors, the author highlights the success and limits of the NAFTA integration model. He concludes that while NAFTA should not be seen as a solution to all of Mexico’s socio-economic problems, NAFTA nonetheless suffers from a "deficient [social] institutionality" that can be addressed through both domestic and supranational reforms. At the domestic level, the Mexican government should rethink its export-led growth strategy and prioritize tax reforms and domestic investments in education and infrastructure. At the supranational level, the NAFTA model should be upgraded to address its social lacunae, especially in the policy spheres of investment, immigration, agriculture, and resource transfers.